Ustekinumab in pediatric patients with Crohn’s disease: safety, and efficacy results from a multicenter retrospective study in China - Li, Ping; Wang, Lin; Tang, Zifei; Wang, Yuhuan; Liu, Zhanju; Ge, Wensong; Huang, Ying (Frontiers in Pediatrics, 2024)
Background Ustekinumab (UST) is approved as an effective therapy for Crohn's disease (CD) in adults. Off-label use is increasing in the pediatric population, more data on safety and efficacy in pediatric patients with CD is urgently needed. Aims This study aimed to evaluate the clinical efficacy and safety of UST in children and adolescents with Crohn's disease. Methods This multicenter retrospective study carried out at three tertiary care centers, and identified children who received their first dose of UST at 18 years old or younger and followed up for a minimum of 24 weeks. Data on demographics, disease behavior, location and activity, treatment history were collected. The primary outcomes were clinical remission at weeks 24 32 and weeks 48 56 of UST therapy. Secondary outcomes were clinical response at the same time points, endoscopic remission, changes in C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), albumin and fecal calprotectin, improvement in growth parameters, and rate of adverse events. Results Sixteen patients were included, and 11/13 (84.6%) continued to receive UST after 1 year. Our data demonstrate that the clinical remission rates were 41.7% at weeks 24 32 with the Weighted pediatric CD activity index (wPCDAI) was lower than baseline (43.8, IQR:31.3-51.9 vs.15, IQR: 5.6-25, p＜0.001) and 75% at weeks 48 56 with wPCDAI was lower than baseline (42.5, IQR: 23.8-50 vs. 7.5, IQR: 0-13.8, p=0.004). Five of eleven children achieved endoscopic remission. No serious adverse events were recorded during the study period. Conclusions UST is efficacious and safe in pediatric patients with CD. Pediatric patients could benefit from UST as either a primary or secondary biologic therapy for the induction, or maintenance of remission of CD.